PENGARUH PEMAKAIAN BAHAN TAMBAH TAWAS PADA AIR RAWA TERHADAP COMPRESSIVE STENGTH BETON - Oemiati, Nurnilam Oemiati; Royan, Noto (Universitas Muhammadiyah Palembang, 2023)
Kenten Laut is a rural locality in the Talang Kelapa District that consists largely of a swamp. Residentsrely heavily on the swamp's corrosive water for mundane concrete mixing. Researchers in this study usedswamp water and alum in the concrete recipe. Swamp water and alum were utilized as the supplementarycomponents, with the alum content of the solution varying between 2% and 4% by weight of cement. Thetest object is a cube with the dimensions (15, 15, and 15) cm and there are fifty of them.Compressive strength testing in swamp water revealed findings of 152.69 kg/cm2 for 14-day-old concreteand 251.93 kg/cm2 for 28-day-old concrete. The compressive strength of 14-day-old swamp water concretevaried between 156.16 kg/cm2 and 149.78 kg/cm2 depending on the percentage of alum added to the mix.Compressive strength values for 28-day-old concrete made with swamp water with 2%, 4%, or 6% alumare 256.19 kg/cm2, 253.97 kg/cm2, and 245.61 kg/cm2, respectively. These numbers are lower than whatwas anticipated for the K-300. Compressive strength in typical concrete drops by 20.6% after 28 days ofage, but only 14.7% after 14 days.